Observation of the turbulent flow in superfluid He-4 using a vibrating wire - Yano, H; Handa, A; Nakagawa, H; Nakagawa, A; Obara, K; Ishikawa, O; Hata, T (2005)
We have investigated the laminar and the turbulent flow in superfluid 4He using a vibrating wire made from a thin NbTi wire (φ 2.5 μm). We measured vibrating velocity of the wire as a function of driving force at 1.4 K and found that the laminar and the turbulent flow around the wire are clearly separated at a critical velocity. This phenomenon suggests that expansion of vortices attached on the wire causes the turbulence and those sizes are limited to an order of microns even in the turbulent flow. This limitation is considered due to tangle and reconnection of the vortices by oscillating flow. The critical velocity varies with frequency of the oscillating flow and the vortices seem to be confined closely at high frequencies. We also found a stable state of the vortices thickly attached on the wire by controlling cool down through the superfluid transition. © 2005 Elsevier Ltd. All rights reserved.